Predictors of patient's intentions to participate in pragmatic clinical trials: An initial exploration. (December 2016) - Gibson, Bryan; Butler, Jorie M.; Lewis, Lacey; Weir, Charlene
Abstract: The Veterans Health Administration is implementing a pragmatic trial research program, called Point of Care Research (POC-R). The purpose of this telephone survey in which respondents were randomized to different framing conditions of the purpose of POC-R was to determine the impact of differing frames of the purpose of POC-R on attitudes towards the program and intentions to participate; and the relative importance of different beliefs and attitudes in discriminating low vs. high intenders to participate in POC-R. The survey addressed veterans' perceptions and attitudes towards POC-R, and their willingness to participate in a pragmatic trial. Overall, respondents felt positively towards POC-R and intended to participate. Differing frames of the purpose of POC-R were not associated with either attitudes (towards the program) or intentions to participate. However, specific beliefs and attitudes toward POC-R program were predictive of intentions to participate.